Desenvolvimento de uma análise das inter-relações entre um sistema de gestão da qualidade e um sistema operacional: um estudo de caso na United Technologies Corporation - Menezes, Thiago Morais (Universidade do Vale do Rio do Sinos, 2009)
This research investigates the Operating System of the United Technologies Corporation - UTC, called ACE, identifying and analyzing their interrelations with the Quality Management System ISO9001. The methodology of this research is characterized by a qualitative approach and case study incorporated, which is conducted in three stages. The first step is a broad description of the ACE Operating System to introduce this system to the academy. The second step is the study of the interrelationship between the two theoretical systems. In the third stage are studied the relationship between the practices prescribed for the two systems in one UTC manufacturing unit. The identification and analysis of the interrelations in this study have made an organized structure that allows the planning of a project of unification of the systems. Another important contribution of this study is the use of the method for analyzing the interrelations between others systems.
Keywords: ISO9001; manufatura enxuta; sistema de gestão; sistema operacional ACE; lean manufacturing; management system; ACE operating system; Engenharias